Pembelajaran Bangun Datar Berbasis Kontekstual Aplikasi Insert Shape untuk Meningkatkan Pemahaman Siswa Sekolah Dasar - Asri Putri Anugraini (Universitas Islam Negeri Sayyid Ali Rahmatullah Tulungagung, 2018)
This study aims to teach students in the use of insert shape facilities through contextual learning on geometry material to improve students' understanding at SDN 1 Panggungerjo Kepanjen. The type of research used by Classroom Action Research. This study was carried out in two cycles and each cycle of three meetings. The research subjects were 45 third grade students of SDN 1 Panggungrejo Kepanjen. Data to be taken are: a) observation results, b) student test results, c) interview results, d) results of field notes. The process of contextual learning with insert shape facilities starts from the initial, core and final activities. The initial activity consisted of researchers grouping students, conveying learning objectives, giving questions, introducing geometry, introducing insert shapes. The core activity, studying the geometry of concrete media, giving assignments, practice insert shape applications, presentations. The final activity is reflection. The results of classroom action research in the first cycle show that the average value of student learning outcomes reached 50%. In cycle II student learning outcomes have increased by 70%. In the second cycle students were very enthusiastic about learning geometry and students could calculate the circumference and area of geometry and could practice computers with insert shape facilities.